Tibial Spine Fractures in Children: Evaluation, Management, and Future Directions - Adams, Alexander J.; Talathi, Nakul S.; Gandhi, Jigar S.; Patel, Neeraj M.; Ganley, Theodore J. (The Journal of Knee Surgery, 2018)
Fractures of the tibial spine are estimated to occur in 3 per 100,000 children annually, but account for 2 to 5% of pediatric knee injuries with effusion. Although these fractures were historically associated with bicycle accidents, the surge of organized youth sports in recent decades has brought renewed attention to this injury. While minimally displaced fractures can be treated nonoperatively, several techniques have been described for fixation of displaced or comminuted fractures. Sequelae of this injury can include arthrofibrosis, knee instability, and nonunion. Future collaborative endeavors will aim to further identify risk factors for these complications to optimize the treatment of tibial spine fractures in children.
Keywords: tibial spine fracture; intercondylar eminence; pediatric sports; pediatric knee